Determinan Terhadap Penggelapan Pajak Melalui Religiulitas Sebagai Pemoderasi - Azzahra Andien Syahrani; Achmad Badjuri (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to examine the effect of money ethics, taxation system, and tax justice on tax evasion with religiosity as a moderating variable. This type of research is quantitative research using primary data obtained from questionnaires distributed to individual taxpayers registered at KPP Pratama Semarang Candisari. Sampling using the slovin formula with a total sample of 125 people. The method of data analysis technique used is multiple linear regression analysis using the SPSS program. The results of this study indicate that money ethics and tax justice have a negative and significant effect on tax evasion, while the tax system has no effect on tax evasion. Religiosity cannot moderate the effect of money ethics and tax justice on tax evasion, while religiosity can moderate the effect of the tax system on tax evasion.